Preparation method and application of carbon-metal particle material

By preparing carbon-metal particulate materials, the performance degradation caused by volume changes in the electrode material in lithium batteries is solved, and the efficient cycle and long life of the battery are achieved.

CN119571283APending Publication Date: 2025-03-07JIANGSU FEYNMAN SEMICON TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411701726.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The volume expansion and contraction of electrode materials in lithium batteries during charging and discharging, resulting in battery capacity decay, reduced cycle life and safety problems.

Method used

The carbon-metal particulate material is prepared by using the preparation method of metal particles, through the compaction of metal particles, thermochemical vapor deposition and post-treatment steps, and the carbon-metal particulate material with high conductivity and stability is formed, and it is applied in batteries.

Benefits of technology

It improves the circulation and energy storage performance of lithium batteries, extends the service life of the battery, and reduces the insecurity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571283A_ABST
    Figure CN119571283A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a carbon-metal particle material, belongs to the field of new material preparation and electrochemical energy storage, and is used for solving the problems of volume expansion and shrinkage of an electrode material in a current lithium battery in a charging and discharging process and improving the cycle performance and the energy storage performance of the lithium battery. The preparation method of the carbon-metal particle material comprises the steps that metal particles are compacted on a substrate and conveyed into a high-temperature furnace, alkane gas is introduced, heating growth is carried out, washing and drying are carried out after growth is completed, and carbon-metal particles I are obtained; the carbon-metal particles I and polydimethylsiloxane are subjected to a reaction, and a carbon-metal particle material is obtained; the carbon-metal particles prepared by the method have good conductivity, stability and flexibility; when the composite material is applied to a battery, pulverization and stripping of an electrode material can be reduced, volume change of the electrode material is reduced, and cycle service life and safety of the battery are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of new material preparation and electrochemical energy storage, and in particular to a preparation method of a carbon-metal particle material and application thereof. Background Art

[0002] In recent years, with the rapid development of society, energy and environmental issues have become two major global problems. At present, a battery that can reduce the degree of environmental pollution and has a good effect in energy storage is increasingly sought after by people. Lithium batteries have the advantages of high operating voltage, relatively light weight, no memory effect, low self-discharge, and long cycle life; lithium-ion batteries do not contain chromium and nickel, which reduces environmental pollution. In recent years, miniaturized devices have increased, and high requirements have been placed on lithium-ion batteries. At the same time, lithium batteries occupy a very important position in the portable battery market.

[0003] According to industry research, lithium batteries account for more than 80% of the market in portable electronic devices such as smartphones, tablets, laptops, and wearable devices. However, the electrode materials of lithium batteries often face the problem of insufficient conductivity, especially when using some low-conductivity materials, the battery's charge and discharge performance and rate will be limited. Among them, powdering and peeling in electrode materials cause battery capacity decay and reduced cycle life. During the charging and discharging process of lithium batteries, the electrode materials will expand and contract. This volume change may cause damage to the electrode structure, thereby affecting the safety of the battery, reducing the battery's energy storage effect, and not conducive to extending the battery's service life. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for preparing a carbon-metal particle material and its application, which solves the problem of volume expansion and contraction of electrode materials in current lithium batteries during charging and discharging, improves the cycle performance and energy storage performance of lithium batteries, and prolongs their service life.

[0005] In order to achieve the above object, the present invention provides a method for preparing a carbon-metal particle material, comprising the following steps:

[0006] Step (1) The metal particles are compacted on the substrate, and the substrate is placed in the middle of a quartz boat, pushed into an integrated dual-temperature zone high-temperature furnace, and an inert gas is introduced and maintained for a period of time; a mixed atmosphere consisting of an inert gas and hydrogen is introduced and maintained for a period of time; an alkane gas is introduced, and the integrated dual-temperature zone high-temperature furnace is heated and grown, and the growth is completed; the introduction of the alkane gas is stopped, the quartz boat is removed, washed, and dried to obtain carbon-metal particles I;

[0007] Step (2) adding carbon-metal particles I and polydimethylsiloxane into anhydrous ethanol, stirring evenly, heating, reacting, and after the reaction is completed, filtering, washing, and drying to obtain a carbon-metal particle material.

[0008] Preferably, the metal in the metal particles is Fe or Ni.

[0009] Preferably, the substrate is a silicon wafer.

[0010] Preferably, the size of the metal particles is 5 nm-20 μm.

[0011] Preferably, the carbon in the carbon-metal particles is any one of graphene and graphite with a thickness of 0.3 nm-10 μm.

[0012] Preferably, the mixed atmosphere contains 70-90 sccm, 99.99% hydrogen and 100-300 sccm, 99.99% argon.

[0013] Preferably, the specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 450-550°C at a heating rate of 10-20°C / min and maintaining for 20-30 minutes; heating from the preheating temperature to 900-1100°C at a heating rate of 10-20°C / min and growing for 15-25 minutes.

[0014] Preferably, the purity of the alkane gas is 5-15%.

[0015] Preferably, in step (1), the washing material is an aqueous solution of n-butanol, and the volume ratio of n-butanol to water is 1:200;

[0016] Preferably, the alkane gas is any one of methane, ethane and propane.

[0017] Preferably, the mass ratio of anhydrous ethanol, carbon-metal particles I and polydimethylsiloxane is (1000-1800):(60-80):(30-50).

[0018] Preferably, in step (2), the reaction conditions are 65-85° C. and the reaction time is 2-4 h.

[0019] Preferably, the carbon-metal particle material is prepared by the method for preparing the carbon-metal particle material.

[0020] Preferably, the carbon-metal particle material is used in a battery.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] In the present invention, metallic iron and nickel have good electrical conductivity in themselves, and the carbon materials on their surfaces include graphene and graphite, both of which have certain electrical conductivity. The combination of the two further improves the overall electrical conductivity, and high electrical conductivity helps to improve the rate performance and charge and discharge efficiency of the battery. Carbon materials can promote the diffusion of lithium ions and provide more reaction sites during the charging and discharging process, thereby enhancing the rate of electrochemical reactions; carbon materials can also serve as storage and release channels for lithium ions, providing better lithium ion embedding and de-embedding paths. In this way, the battery reacts more efficiently during charging and discharging, further improving energy utilization. The carbon material on the surface of the metal particles not only improves stability due to its high temperature resistance, but also prevents aggregation between metal particles, prevents the particles from falling off and agglomerating, improves the stability of the structure during the charging and discharging process of the lithium battery, and improves the cycle life of the battery. The added flexible polydimethylsiloxane has a relatively large bond energy of silicon-oxygen bonds, which can further improve the stability of the carbon-metal particle material and help the battery to continue to work normally at higher temperatures; due to its flexibility, polydimethylsiloxane can work together with carbon materials to improve the stability of the carbon-metal particle material, reduce the volume change of the electrode material, reduce stress concentration, and prevent damage to the carbon-metal particle material or the electrode material prepared therefrom, so that the electrode can maintain good mechanical stability and structural integrity during multiple charge and discharge processes, reduce the degree of peeling or pulverization of the electrode material after the electrode material undergoes expansion and contraction, and is beneficial to the battery cycle life and safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a bar graph of the capacity retention rate of sample 1 and sample 2 after 100 charge and discharge cycles in the present invention. DETAILED DESCRIPTION

[0024] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] This embodiment provides a method for preparing a carbon-metal particle material, comprising the following steps:

[0027] Step (1) Fe metal particles with a size of 5 nm are compacted on a silicon wafer, and the silicon wafer is placed in the middle of a quartz boat, pushed into an integrated dual-temperature zone high-temperature furnace, and argon gas of 99.99% is introduced for 10 minutes; a mixed atmosphere consisting of 70 sccm, 99.99% hydrogen and 100 sccm, 99.99% argon is introduced and maintained for 50 minutes; methane with a purity of 5% is introduced, and an integrated dual-temperature zone high-temperature furnace is set up for heating and growth, and the growth is completed; the introduction of methane is stopped, cooled to room temperature, the quartz boat is removed, and washed with an aqueous solution of n-butanol composed of n-butanol and water in a volume ratio of 1:200 for 10 minutes, and dried at 60°C for 6 hours to obtain carbon-metal particles I;

[0028] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 450°C at a heating rate of 10°C / min and maintaining for 30 minutes; heating from the preheating temperature to 900°C at a heating rate of 10°C / min and growing for 25 minutes;

[0029] Step (2) mixing anhydrous ethanol, carbon-metal particles I and polydimethylsiloxane in a mass ratio of 1000:60:30, reacting at 65° C. for 4 h, and after the reaction, filtering, washing with deionized water, and drying at 90° C. for 8 h to obtain a carbon-metal particle material;

[0030] The carbon in the carbon-metal particle material is graphene with a thickness of 0.82 nm.

[0031] Example 2

[0032] This embodiment provides a method for preparing a carbon-metal particle material, comprising the following steps:

[0033] Step (1) Fe metal particles with a size of 10 μm are compacted on a silicon wafer, and the silicon wafer is placed in the middle of a quartz boat, pushed into an integrated dual-temperature zone high-temperature furnace, and argon gas of 99.99% is introduced for 15 minutes; a mixed atmosphere consisting of 80 sccm, 99.99% hydrogen and 200 sccm, 99.99% argon is introduced and maintained for 40 minutes; methane with a purity of 10% is introduced, and an integrated dual-temperature zone high-temperature furnace is set for heating and growth, and the growth is completed; the introduction of methane is stopped, cooled to room temperature, the quartz boat is removed, and washed with an aqueous solution of n-butanol composed of n-butanol and water in a volume ratio of 1:200 for 15 minutes, and dried at 70°C for 5 hours to obtain carbon-metal particles I;

[0034] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 500°C at a heating rate of 15°C / min and maintaining for 25 minutes; heating from the preheating temperature to 1000°C at a heating rate of 15°C / min and growing for 20 minutes;

[0035] Step (2) mixing anhydrous ethanol, carbon-metal particles I and polydimethylsiloxane in a mass ratio of 1400:70:40, reacting at 75° C. for 3 h, and after the reaction, filtering, washing with deionized water, and drying at 100° C. for 7 h to obtain a carbon-metal particle material;

[0036] The carbon in the carbon-metal particle material is graphene with a thickness of 4.5 μm.

[0037] Example 3

[0038] This embodiment provides a method for preparing a carbon-metal particle material, comprising the following steps:

[0039] Step (1) Fe metal particles with a size of 20 μm are compacted on a silicon wafer, and the silicon wafer is placed in the middle of a quartz boat, pushed into an integrated dual-temperature zone high-temperature furnace, and argon gas of 99.99% is introduced for 20 minutes; a mixed atmosphere consisting of 90 sccm, 99.99% hydrogen and 300 sccm, 99.99% argon is introduced and maintained for 30 minutes; methane with a purity of 15% is introduced, and an integrated dual-temperature zone high-temperature furnace is set for heating and growth, and the growth is completed; the introduction of methane is stopped, cooled to room temperature, the quartz boat is removed, and washed with an aqueous solution of n-butanol composed of n-butanol and water in a volume ratio of 1:200 for 20 minutes, and dried at 80°C for 4 hours to obtain carbon-metal particles I;

[0040] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 550°C at a heating rate of 20°C / min and maintaining for 20 minutes; heating from the preheating temperature to 1100°C at a heating rate of 20°C / min and growing for 15 minutes;

[0041] Step (2) mixing anhydrous ethanol, carbon-metal particles I and polydimethylsiloxane in a mass ratio of 1800:80:50, reacting at 85° C. for 2 h, and after the reaction, filtering, washing with deionized water, and drying at 110° C. for 6 h to obtain a carbon-metal particle material;

[0042] The carbon in the carbon-metal particle material is graphene with a thickness of 10 μm.

[0043] Example 4

[0044] This embodiment provides a method for preparing a carbon-metal particle material, comprising the following steps:

[0045] Step (1) Ni metal particles with a size of 5 nm are compacted on a silicon wafer, and the silicon wafer is placed in the middle of a quartz boat, pushed into an integrated dual-temperature zone high-temperature furnace, and argon gas of 99.99% is introduced for 10 minutes; a mixed atmosphere consisting of 70 sccm, 99.99% hydrogen and 100 sccm, 99.99% argon is introduced and maintained for 50 minutes; methane with a purity of 5% is introduced, and an integrated dual-temperature zone high-temperature furnace is set for heating and growth, and the growth is completed; the introduction of methane is stopped, cooled to room temperature, the quartz boat is removed, and washed with an aqueous solution of n-butanol composed of n-butanol and water in a volume ratio of 1:200 for 10 minutes, and dried at 60°C for 6 hours to obtain carbon-metal particles I;

[0046] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 450°C at a heating rate of 10°C / min and maintaining for 30 minutes; heating from the preheating temperature to 900°C at a heating rate of 10°C / min and growing for 25 minutes;

[0047] Step (2) mixing anhydrous ethanol, carbon-metal particles I and polydimethylsiloxane in a mass ratio of 1000:60:30, reacting at 65° C. for 4 h, and after the reaction, filtering, washing with deionized water, and drying at 90° C. for 8 h to obtain a carbon-metal particle material;

[0048] The carbon in the carbon-metal particle material is graphene with a thickness of 0.65 nm.

[0049] Example 5

[0050] This embodiment provides a method for preparing a carbon-metal particle material, comprising the following steps:

[0051] Step (1) Ni metal particles with a size of 10 μm are compacted on a silicon wafer, and the silicon wafer is placed in the middle of a quartz boat, pushed into an integrated dual-temperature zone high-temperature furnace, and argon gas of 99.99% is introduced for 15 minutes; a mixed atmosphere consisting of 80 sccm, 99.99% hydrogen and 200 sccm, 99.99% argon is introduced and maintained for 40 minutes; methane with a purity of 10% is introduced, and an integrated dual-temperature zone high-temperature furnace is set for heating and growth, and the growth is completed; the introduction of methane is stopped, cooled to room temperature, the quartz boat is removed, and washed with an aqueous solution of n-butanol composed of n-butanol and water in a volume ratio of 1:200 for 15 minutes, and dried at 70°C for 5 hours to obtain carbon-metal particles I;

[0052] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 500°C at a heating rate of 15°C / min and maintaining for 25 minutes; heating from the preheating temperature to 1000°C at a heating rate of 15°C / min and growing for 20 minutes;

[0053] Step (2) mixing anhydrous ethanol, carbon-metal particles I and polydimethylsiloxane in a mass ratio of 1400:70:40, reacting at 75° C. for 3 h, and after the reaction, filtering, washing with deionized water, and drying at 100° C. for 7 h to obtain a carbon-metal particle material;

[0054] The carbon in the carbon-metal particle material is graphene with a thickness of 3.2 μm.

[0055] Example 6

[0056] This embodiment provides a method for preparing a carbon-metal particle material, comprising the following steps:

[0057] Step (1) Ni metal particles with a size of 20 μm are compacted on a silicon wafer, and the silicon wafer is placed in the middle of a quartz boat, pushed into an integrated dual-temperature zone high-temperature furnace, and argon gas of 99.99% is introduced for 20 minutes; a mixed atmosphere consisting of 90 sccm, 99.99% hydrogen and 300 sccm, 99.99% argon is introduced and maintained for 30 minutes; methane with a purity of 15% is introduced, and an integrated dual-temperature zone high-temperature furnace is set for heating and growth, and the growth is completed; the introduction of methane is stopped, cooled to room temperature, the quartz boat is removed, and washed with an aqueous solution of n-butanol composed of n-butanol and water in a volume ratio of 1:200 for 20 minutes, and dried at 80°C for 4 hours to obtain carbon-metal particles I;

[0058] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 550°C at a heating rate of 20°C / min and maintaining for 20 minutes; heating from the preheating temperature to 1100°C at a heating rate of 20°C / min and growing for 15 minutes;

[0059] Step (2) mixing anhydrous ethanol, carbon-metal particles I and polydimethylsiloxane in a mass ratio of 1800:80:50, reacting at 85° C. for 2 h, and after the reaction, filtering, washing with deionized water, and drying at 110° C. for 6 h to obtain a carbon-metal particle material;

[0060] The carbon in the carbon-metal particle material is graphene with a thickness of 8.9 μm.

[0061] Example 7

[0062] This embodiment provides a method for preparing a carbon-metal particle material, comprising the following steps:

[0063] Step (1) Fe metal particles with a size of 5 nm are compacted on a silicon wafer, and the silicon wafer is placed in the middle of a quartz boat, pushed into an integrated dual-temperature zone high-temperature furnace, and argon gas of 99.99% is introduced for 15 minutes; a mixed atmosphere consisting of 85 sccm, 99.99% hydrogen and 150 sccm, 99.99% argon is introduced and maintained for 30 minutes; methane with a purity of 10% is introduced, and an integrated dual-temperature zone high-temperature furnace is set for heating and growth, and the growth is completed; the introduction of methane is stopped, cooled to room temperature, the quartz boat is removed, and washed with an aqueous solution of n-butanol composed of n-butanol and water in a volume ratio of 1:200 for 10 minutes, and dried at 60°C for 6 hours to obtain carbon-metal particles I;

[0064] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 480°C at a heating rate of 13°C / min and maintaining for 30 minutes; heating from the preheating temperature to 980°C at a heating rate of 13°C / min and growing for 18 minutes;

[0065] Step (2) mixing anhydrous ethanol, carbon-metal particles I and polydimethylsiloxane in a mass ratio of 1000:60:30, reacting at 65° C. for 4 h, and after the reaction, filtering, washing with deionized water, and drying at 90° C. for 8 h to obtain a carbon-metal particle material;

[0066] The carbon in the carbon-metal particle material is graphite with a thickness of 0.42 nm.

[0067] Example 8

[0068] This embodiment provides a method for preparing a carbon-metal particle material, comprising the following steps:

[0069] Step (1) Ni metal particles with a size of 5 nm are compacted on a silicon wafer, and the silicon wafer is placed in the middle of a quartz boat, pushed into an integrated dual-temperature zone high-temperature furnace, and argon gas of 99.99% is introduced for 15 minutes; a mixed atmosphere consisting of 85 sccm, 99.99% hydrogen and 150 sccm, 99.99% argon is introduced and maintained for 30 minutes; methane with a purity of 10% is introduced, and an integrated dual-temperature zone high-temperature furnace is set for heating and growth, and the growth is completed; the introduction of methane is stopped, cooled to room temperature, the quartz boat is removed, and washed with an aqueous solution of n-butanol composed of n-butanol and water in a volume ratio of 1:200 for 10 minutes, and dried at 60°C for 6 hours to obtain carbon-metal particles I;

[0070] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 480°C at a heating rate of 13°C / min and maintaining for 30 minutes; heating from the preheating temperature to 980°C at a heating rate of 13°C / min and growing for 18 minutes;

[0071] Step (2) mixing anhydrous ethanol, carbon-metal particles I and polydimethylsiloxane in a mass ratio of 1000:60:30, reacting at 65° C. for 4 h, and after the reaction, filtering, washing with deionized water, and drying at 90° C. for 8 h to obtain a carbon-metal particle material;

[0072] The carbon in the carbon-metal particle material is graphite with a thickness of 0.3 nm.

[0073] Comparative Example 1

[0074] This comparative example provides a method for preparing a carbon-metal particle material, comprising the following steps:

[0075] Step (1) Fe metal particles with a size of 5 nm are compacted on a silicon wafer, and the silicon wafer is placed in the middle of a quartz boat, pushed into an integrated dual-temperature zone high-temperature furnace, and argon gas of 99.99% is introduced for 10 minutes; a mixed atmosphere consisting of 70 sccm, 99.99% hydrogen and 100 sccm, 99.99% argon is introduced and maintained for 50 minutes; methane with a purity of 5% is introduced, and an integrated dual-temperature zone high-temperature furnace is set for heating and growth, and the growth is completed; the introduction of methane is stopped, cooled to room temperature, the quartz boat is removed, and washed with an aqueous solution of n-butanol composed of n-butanol and water in a volume ratio of 1:200 for 10 minutes, and dried at 60°C for 6 hours to obtain carbon-metal particles;

[0076] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 450°C at a heating rate of 10°C / min and maintaining for 30 minutes; heating from the preheating temperature to 900°C at a heating rate of 10°C / min and growing for 25 minutes;

[0077] The carbon in the carbon-metal particle material is graphene with a thickness of 0.82 nm.

[0078] The carbon-metal particle material prepared in Example 1 and Comparative Example 1 was tested: N-methylpyrrolidone, carbon-metal particle material and polyvinylidene fluoride were mixed in a mass ratio of 5:2:1 to obtain a slurry; and the slurry was evenly pressed on a copper foil disc; the working electrode was dried for the first time at 85°C for 6 hours in a vacuum oven, and dried for the second time at 125°C for 3 hours to obtain battery negative electrode 1 and battery negative electrode 2; the battery separator was a polypropylene film, and the electrolyte was LiPF6 with 50μL added. Battery negative electrode 1 and battery negative electrode 2 were used as lithium battery negative electrode materials, LiCoO2 was used as lithium battery positive electrode, and assembled with CR2032 accessories to obtain lithium batteries, which were recorded as sample 1 and sample 2 respectively. The initial lithium battery capacity was tested by constant current charge and discharge method, and the capacity of the lithium battery after 50 and 100 cycles of continuous charge and discharge was recorded. The capacity retention rate of the lithium battery was recorded, and repeated three times, and the average value was taken and recorded. The specific test results are shown in Table 1;

[0079] Table 1

[0080]

[0081] It can be seen from the test results in Table 1 that the carbon-metal particle material prepared by the present invention has a good effect in lithium batteries, which can improve the capacity retention rate of lithium batteries and increase the service life of batteries. The carbon in the carbon-metal particle material in Sample 1 is graphene, which reacts with polydimethylsiloxane to further increase thermal stability, improve flexibility, reduce expansion and contraction of electrode materials during charging and discharging, and help reduce the probability of expansion and contraction of electrode materials, reduce the insecurity of batteries, and help the energy storage effect of batteries. Once it is lacking, the battery performance will naturally decrease.

[0082] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a carbon-metal particle material, characterized in that: The following steps are involved: Step (1) The metal particles are compacted on the substrate, and the substrate is placed in the middle of a quartz boat, pushed into an integrated dual-temperature zone high-temperature furnace, and an inert gas is introduced and maintained for a period of time; a mixed atmosphere consisting of an inert gas and hydrogen is introduced and maintained for a period of time; an alkane gas is introduced, and the integrated dual-temperature zone high-temperature furnace is heated and grown, and the growth is completed; the introduction of the alkane gas is stopped, the quartz boat is removed, washed, and dried to obtain carbon-metal particles I; Step (2) adding carbon-metal particles I and polydimethylsiloxane into anhydrous ethanol, stirring evenly, heating, reacting, and after the reaction is completed, filtering, washing, and drying to obtain a carbon-metal particle material.

2. The method for preparing a carbon-metal particle material according to claim 1, characterized in that: The metal in the metal particles is Fe or Ni.

3. The method for preparing a carbon-metal particle material according to claim 1, characterized in that: The carbon in the carbon-metal particles is any one of graphene and graphite with a thickness of 0.3 nm to 10 μm.

4. The method for preparing a carbon-metal particle material according to claim 1, characterized in that: The mixed atmosphere contains 70-90 sccm of 99.99% hydrogen and 100-300 sccm of 99.99% argon.

5. The method for preparing a carbon-metal particle material according to claim 1, characterized in that: The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 450-550°C at a heating rate of 10-20°C / min and maintaining for 20-30 minutes; heating from the preheating temperature to 900-1100°C at a heating rate of 10-20°C / min and growing for 15-25 minutes.

6. The method for preparing a carbon-metal particle material according to claim 1, characterized in that: The purity of the alkane gas is 5-15%.

7. The method for preparing a carbon-metal particle material according to claim 1, characterized in that: The mass ratio of anhydrous ethanol, carbon-metal particles I and polydimethylsiloxane is (1000-1800):(60-80):(30-50).

8. The method for preparing a carbon-metal particle material according to claim 1, characterized in that: In step (2), the reaction conditions are 65-85° C. and the reaction time is 2-4 h.

9. A carbon-metal particle material prepared by the method for preparing a carbon-metal particle material according to any one of claims 1 to 8.

10. Use of the carbon-metal particle material according to claim 9 in a battery.